Zmiany w sprawozdaniu finansowym jednostek budżetowych i ich wpływ na ewidencję kosztów - Rudnicka, Bożena (Changes in Financial Statement of Budgetary Units and Their Influence on Cost Accounting, 2007)
To the end of 2005 the financial statement of budgetary units consisted only of balance sheet. According to new regulations for the first time this statement for 2006 will be also including profit and loss account and the rules of its proper making. In practise a lot of positions especially of profit and loss account raise reasoned doubts about their content and the rules of proper making. Analising composition and content of financial statement made by budgetary units on account of convergence with the content of corresponding elements of the financial statement of income units, one has to take under consideration specificity of functioning of units from public finance sector to adequately evaluate information included in this statement. It is so because in many cases basing only on the knowledge of content of financial statement of income units, one can draw wrong conclusions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 269-279